Valor nutritivo de forrageiras tropicais com diferentes períodos de rebrota - Barreto, Julio Cezar (2012)
In experiment 1 were evaluated low-quality hay, in beef cattle feeding to beef cattle considering ruminal digestibility, intestinal and total nutrients, the apparent absorption of phosphorus, the ruminal degradability of dry matter (DM), crude protein ( CP) and phosphorus (P), the fermentation parameters and kinetics, the efficiency of microbial protein synthesis in rumen and some serum parameters. There were used four Nellore, castrated, 413 ± 54 kg of body weight (BW), fitted with ruminal cannula randomly distributed in a randomized 4 x 4 Latin square. Hays were: Cynodon dactylon (Tifton 85), Cynodon nlemfuensis (Star-purple), Brachiaria decumbens and Brachiaria brizantha. All animals received protein mineral supplement to meet the minimum requirements of protein and minerals. The total dry matter (DM) did not differ between hays. Hays had apparent digestibility coefficients for dry matter, of 0.476 g / g. The phosphorus intake of animals fed with Brachiaria brizantha hay was higher, but the apparent total P uptake was similar among hays. For crude protein was observed higher intake for animals receiving hay of Brachiaria decumbens. The hays were similar, and the fermentation kinetics, the efficiency of microbial protein synthesis and serum parameters (phosphorus, calcium, and plasma urea nitrogen) were not affected by hay. In experiments 2 and 3, were evaluated chemical composition, nutritional value, digestibility, intestinal protein and intestinal disappearance of P using in vitro technique, and degradability of DM, CP and P of Brachiaria (Experiment 2) and Panicum ( Experiment 3) grasses at different ages of regrowth (30, 45 and 60 days), with and without fertilization. There were evaluated three plots of each species. For experiment 2: Brachiaria humidicola cv. Llanero, Brachiaria decumbens cv. Basilisk, Brachiaria brizantha cv. Piata and Brachiaria brizantha cv. Marandu. Cultivars Llanero and Marandu had the highest crude protein, and Marandu grass had the lowest content of neutral detergent fiber (NDF) Llanero had the lowest level of non-fiber carbohydrates (NFC), while decumbens showed the highest carbohydrate content total (TC) Piata had the lowest level of P. The in vitro digestibility of organic matter (IVOMD) and total digestible nutrients (TDN) were higher at 30 days of age, and Piata grass had the lowest IVOMD and TDN. The forages differed in their intestinal digestibility of CP at 60 days of regrowth. The forage Llanero had the lowest intestinal disappearance of P and the highest disappearance rates for 30 days. The effective degradability (ED) of DM was lower for Decumbens and ED of CP was higher for Llanero and Marandu grasses. The higher soluble fraction of P was obtained for Llanero grass. With the advancement of age the regrowth decreased DM and CP. In experiment 3 were evaluated Panicum maximum, Tanzania, Mombasa and Massai. The cultivars showed no differences in fertilization. The higher DM and OM and lower P concentrations were obtained for Massai grass. The ages of regrowth influence the chemical composition of the cultivars. There was interaction between cultivars and ages of regrowth for NDF and TDN. The highest NDF values were observed at 60 days, and Massai showed higher contents of NDF and did not differ between the ages of regrowth, whileNDF of Mombasa and Tanzania increased with the age. Regardless of cultivar, higher TDN values were obtained after 30 days of regrowth. The Tanzania grass showed higher IVOMD than Mombasa and the DIVIPB was higher to Massai compared to Mombasa. The highest DIVIP was to Massai. The higher IVOMD was obtained at 30 days, falling sharply to 45 days. The Massai grass had higher DM then Mombasa grass. The Tanzania grass showed higher ED of CP than Massai grass. The fractions for DM and ED of CP were higher at 30 days of regrowth.